Prospective teacher online assessment literacy of English Language Education study program at Undiksha - Putri, Putu Jesika Suwendra; Paramartha, A.A. Gede Yudha; Wahyuni, Luh Gede Eka (English Education Department STKIP Agama Hindu Singaraja, 2024)
The role of prospective teachers continues to evolve alongside advancements in education and technology. As digital learning environments become more prevalent, educators must be equipped with essential competencies, including online assessment literacy. This study examines the level of online assessment literacy among sixth-semester prospective teachers in the English Language Education Program at Universitas Pendidikan Ganesha (Undiksha). Given the increasing reliance on digital assessment tools, understanding prospective teachers' readiness is crucial for effective teaching and learning. This research involved 73 students who had completed assessment courses, utilizing a structured questionnaire to measure their proficiency across seven key dimensions of assessment. The findings indicate that most participants demonstrate a moderate level of online assessment literacy. On average, female students scored 50.5%, while male students scored 46.4%. The highest score among female students was in the Recognizing Ethics (RE) dimension (62.7%), whereas male students scored highest in the Communicating (CO) dimension (55.6%). Conversely, the lowest scores were recorded in the Developing (DE) dimension, with 36.8% for females and 31.9% for males, indicating difficulties in designing effective assessment tools. These findings highlight the need for practical training that enhances digital assessment competencies. Integrating workshops, digital assessment simulations, and targeted pedagogical training into the curriculum can help bridge the gap between theoretical knowledge and practical application. This research provides valuable insights for teacher training programs, ensuring prospective educators are well-prepared for digital assessment challenges.